A small review on polymerase chain reaction for the detection of Salmonella species - Jayanta Deb,, Saurabh Gupta, Sanjit Debnath (Journal of Applied Pharmaceutical Science, 2024)
Salmonella identification from blood samples is crucial for rapid detection and efficient medication of typhoid and paratyphoid fever. Because of its remarkable sensitivity and specificity, polymerase chain reaction (PCR) is a broadly applied technology. The goal of this analysis of 16 papers concentrating on PCR-based Salmonella species identification in blood samples is to identify the most common and successful PCR techniques. The review covers a variety of PCR methods, such as one-step differential detection PCR, nested PCR, multiplex PCR, and real-time PCR. The effectiveness of many PCR primers, including those for the flagellin gene, hilA gene, invA gene, and iroB gene, in detecting Salmonella was examined. The examined studies consistently showed that the PCR techniques used had good sensitivity (95%–100%) and specificity (97%–100%). In addition, PCR was effectively used by the researchers to identify particular species of Salmonella serovars, which comprise Salmonella typhimurium, Salmonella paratyphi A, and Salmonella enteritidis. Notably, multiplex PCR became a useful technique for detecting many Salmonella serovars at the same time. The use of PCR in identifying antibiotic resistance in Salmonella isolates is also emphasized in the review. The collective results highlight the remarkable specificity and sensitivity of PCR-based techniques for Salmonella species identification from blood samples. Of them, real-time PCR and multiplex PCR are the most widely used because of their increased efficiency, sensitivity, and specificity.
Keywords: Salmonella species, polymerase chain reaction, efficacy of techniques, typhoid